Tour guide robot: a 5G-enabled robot museum guide - Rosa, Stefano; Randazzo, Marco; Landini, Ettore; Bernagozzi, Stefano; Sacco, Giancarlo; Piccinino, Mara; Natale, Lorenzo (Frontiers in Robotics and AI, 2024)
This paper presents and discusses the development and deployment of a tour guide robot as part of the 5 g-TOURS EU research project, aimed at developing applications enabled by 5G technology in different use cases. The objective is the development of an autonomous robotic application where intelligence is off-loaded to a remote machine via 5G network, so as to lift most of the computational load from the robot itself. The application uses components that have been widely studied in robotics, (i.e., localization, mapping, planning, interaction). However, the characteristics of the network and interactions with visitors in the wild introduce specific problems which must be taken into account. The paper discusses in detail such problems, summarizing the main results achieved both from the methodological and the experimental standpoint, and is completed by the description of the general functional architecture of the whole system, including navigation and operational services. The software implementation is also publicly available.